(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2008)
Engineering-dominated practices, visible in a "command and control" outlook on natural systems, have induced enormous damage to the environment. Biodiversity losses and declining provision of ecosystem services are testimony to the non-sustainable outcomes brought about by such practices. More environmentally friendly approaches that promote a harmonious relationship between human activities and nature are required. Moves towards an "ecosystem approach" to environmental management require coherent (integrative) scientific guidance. Geomorphology, the study of the form of the earth, provides a landscape template with which to ground this process. This way of thinking respects the inherent diversity and complexity of natural systems. Examples of the transition toward such views in environmental practice are demonstrated by the use of science to guide river management, emphasising applications of the River Styles framework.